Spin in the Media - the Media in a (self-)Spin? - Kristensen, Nete Nørgaard (MedieKultur: Journal of media and communication research, 2006)
The article focuses on the discussion of spin in the Danish media, especially during the 2005 election campaign, in which spin was a prominent issue amongst journalists. The main argument is that this is not primarily an expression of a professional, self-reflective con- sciousness regarding the shifts in the relationship between the media, society and politics. Rather, it is an expression of a self-legitimizing meta-discourse that might, however, fail to see the more structurally rooted tendencies that spin is part of - a mediatization of politics - presenting new perspectives and challenges for both politics and the media. These perspectives appear to disintegrate in the comprehen- sive but often one-dimensional and self-centered discourse of jour- nalists and communication experts, wherein they proclaim every political, communicative initiative as spin in the hunt for the disclosure of political facade.